Evaluation on Habaring Hurung Pier Pontoon to Improve Service in East Kotawaringin Transport System, Central Kalimantan Province - Nur Fareha Binti Mohamad Zukri; Kodrat Alam; M.Noor Rizki Hidayat (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2019)
East Kotawaringin has a relatively large area, namely 16.796 km2 or 10.94 percent of the area of ​​Central Kalimantan province. With an area of ​​regional the East Kotawaringin divided into 17 districts, mostly lowlands. Kotawaringin East region which thousands of cities in Sampit City astronomically lies between 112⁰ 7 '29